Materializing the Hidden Identity of Hong Kong: Re-connecting Hong Kong's vanishing fishing community through urban interventions on the Tam Gong Festival route in Shau Kei Wan - Ma, Florence (University of Waterloo, 2023)
Against the backdrop of the expanding metropolis of Hong Kong, many functioning members of contemporary society have concealed facets of themselves that they now deem irrelevant to their daily lives. Over the last half a century, dramatic changes in Hong Kong’s urban form and industrial life have enticed fisherfolk out of their traditional way of life, dwelling in harbours and on the sea, resulting in the community and individuals moving on land and losing their sense of unique identity. Once forming the famous floating cities in Hong Kong, the community has since been broken up and displaced to the different corners of the metropolis, their presence now barely recognizable to outsiders. The fisherfolk community faces many challenges promoting their collective identity continually with their lack of on-land architectural presence. Instead of focusing on the more permanent architectural elements, this thesis will investigate one of the main deity celebrations, the Tam Kung Festival, in the neighbourhood of Shau Kei Wan, where the presence of the community expands and contracts throughout the year. Combined with the effort of identifying traces of the fishing community buried in the contemporary urban fabric, urbanized traditional ceremonies can be used to build on the existing traces to create new imprints for others to discover the fisherfolk culture. Together, one can weave meaning and memory into the city fabric. Additionally, by learning from the historic nature of the traditional rhythm and fluidity of the fishing community’s lifestyle, we can better understand how to celebrate the different facets of one’s identity. I used mapping exercises based on historical documents, including official maps and annual government reports to help explain the community’s rise and decline and to reveal its shifting presence over a 50-year period in Hong Kong’s growth. I then illustrated the various elements of the Tam Kung Festival to showcase the magical transformation of the streetscape during these special occasions. These drawings, alongside street views and walks, helped me identify what kind of temporary and permanent markers could enhance the urban streetscape for both the fisherfolk and the general public. These elements and the festival act as a spatial catalyst that helps individuals recognize themselves as belonging to the fisherfolk community. By examining and redesigning both permanent and temporary elements of the festival, this thesis proposes a way to aid and expand the presence of the Tam Kung Festival, allowing for the continuous growth and identity renewal of the existing and new members of the fisherfolk community.
Keywords: Hong Kong; Fishing Community; Shau Kei Wan; Tam Kung Festival; Chinese Festivals; Community Identity; Land Reclamation; Urban Development; Aldrich Bay; Bamboo Construction; Fisherfolk; Tanka People; Boat People; Boat Dwellers; Temporary Architecture